2011
DOI: 10.1007/s12098-011-0553-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Specific Learning Disabilities Among Primary School Children in a South Indian City

Abstract: This study suggests that the prevalence of SpLDs is at the higher side of previous estimations in India. The study is unique due to its large geographically representative design and identification of the problem using simplified screening approach and tools, which minimizes the number and time of specialist requirement and spares the expensive investigation. This approach and tools are suitable for field situations and resource scarce settings. Based on the authors' experience, they express the need for more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 17 publications
1
44
1
7
Order By: Relevance
“…In the present study, among the school children in Jaipur, the prevalence of dyslexia is found to be 7.43%. These findings are supported by the studies done by Mogasale et al 26 ., Choudhary et al 27 ., Roongpraiwan et al 18 . Shayawitz et al 17 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, among the school children in Jaipur, the prevalence of dyslexia is found to be 7.43%. These findings are supported by the studies done by Mogasale et al 26 ., Choudhary et al 27 ., Roongpraiwan et al 18 . Shayawitz et al 17 .…”
Section: Discussionsupporting
confidence: 89%
“…These differences may be due to the fact that difference in methods and tools used, sample taken from different geographical areas that varied with respect to age, language and size of the sample. Apart from these studies many researchers 34,35,36,37,38,39,30,26,27,13 have focused on prevalence of learning disabilities which includes dyslexia, dyscalculia and dysgraphia. They have reported a prevalence of 2 to 17.5% which also support above results.…”
Section: Discussionmentioning
confidence: 99%
“…SLD may lead to a host of educational problems. In order to fully understand SLD, the social, emotional and behavioral areas of children's lives need to be considered (Peters, 2011) a point that is neglected by most teachers (Mogasale, Patil, Patil, & Mogasale, 2012). If the disorder is not diagnosed and treated properly, the risk of developing other problems like depression, stress and delinquency increases.…”
mentioning
confidence: 99%
“…Estimates for learning disabilities vary depending on the method of data collection, resulting in significantly different prevalence rates even within the same country. For example, a study in Belgaum, India, found that 15 percent of primary school students between the ages of 8 and 11 had some form of learning disability (Mogasale et al, 2012). Another study in Kerala, India, which identified students through local teachers in a different city, estimated that only 2 percent of students had a learning disability (Gafoor, 2015).…”
Section: Defining Learning Disabilities and High-incidence Disabilitiesmentioning
confidence: 99%